The Mediating Effect Of Human Resource Management In The Relationship Between Organizational Learning Culture With Organizational Citizenship Behavior And Work Engagement - Mohd Ali Bin Hindia (Universiti Sains Islam Malaysia, 2024)
Over the last decade, many researches had been conducted to examine the factors that effects human resource management in organization. However, the mediating effect of human resource management in the relationship between organizational learning culture had not adequately tested, particularly in the context of Malaysia. In recent years, significant remarks have been verified and well documented in organizing the human resource management (HRM) and the relationship between organizational performance by the previous studies. However, researcher has called for the investigation of the mediating effect of human resource management outcomes such as in the relationship between organizational learning culture with organizational citizenship behavior, and work engagement. Most of the previous studies have been conducted in the Western countries and revealed a significance relationship between human resource management and employee's work engagement. However, such relationship has not yet empirically examined. This study is conducted to addresses the gaps were highlighted. The data, were collected though survey from the government agency employees those who are working at Yayasan Sabah, in East Malaysia. There were 214 useable responses obtained are used for further analysis. The data was analyzed with Statistical Package for the Social Sciences (SPSS) version 22 software, to examine the research framework such as tools application conducting exploratory factor analysis. These tools are used to ensure that data is free from any violation of the assumptions such as normality, outliers, multicollinearity, linearity and homoscedasticity. The major outcomes show that the organizational learning culture has an important role as a predictor of human resource management, and significant relationship between organizational citizenship behavior and work engagements. And finally, the Human resource management also appear to have a mediating role as originally proposed.